Relationship between the national evaluation system and the performance of Brazilian rowers - da Silva, F. B. M.; Sacramento Campos, M.; Ribeiro Soares, G.; Gomes, A. C.; Torres, F. C. (Revista Brasileira de Medicina do Esporte, 2020)
Introduction: The National Rower Evaluation System [Sistema Nacional de Avaliação do Remador] (SNAR), adopted by the Brazilian Rowing Confederation, aims to establish a national ranking, and is a prerequisite to participation in National Championships and Selective Games, in its different categories, as well as for joining the Brazilian Rowing Team.